International background, school attendance and early school leavers in Icelandic upper secondary schools 2001–2021 - Garðarsdóttir, Ólöf; Rúnarsdóttir, Eyrún María; Hauksson, Guðjón (Netla, 2022)
Reducing early school leaving has been one of the main priorities of European states in the field of education in recent years. The proportion of early school leavers has been higher in Iceland than among its Nordic neighbours and only a few European countries have higher drop-out rates than Iceland. Icelandic education authorities defined two principal goals in 2014, in which one was for 60% of upper secondary students to graduate on time by the year 2018. At the time, 44% reached this level. This study investigates upper secondary school attendance in two cohorts, one born between 1985–88, the other ten years later (1995–98). Our dataset includes all individuals in those cohorts who lived in Iceland the year they completed elementary school, i.e., the year they turned 16. The focus is on gender and ethnic background.When the first cohort started school, important changes in international migration patterns in Iceland were taking place. Iceland became part of the European Economic Area in the early 1990s which eventually changed the profile of the immigrant population. Until the late 1990s, however, immigrants were few in Iceland, but this changed with the economic boom in the first decade of a new century accompanied by a growing demand for workers, in particular in the construction sector. The economic recession, starting in 2008, had only little and temporary negative impact on the proportion of immigrant population in Iceland and in 2021 15.5% of Iceland’s population were immigrants as compared to 3.6% in 2001.The relatively recent transformation of Icelandic society into an immigrant country can be seen when looking at the age structure of the immigrant population. Currently, almost one out of three inhabitants in their late 20s and early 30s are immigrants, whereas immigrants only account for 6.9% of the population in the age group 15–19 years (compared to 1.7 % in 2001). As for second generation immigrants, the share is even lower. In the study we also focus on other groups with international ...